2021
DOI: 10.1016/j.jvacx.2021.100102
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and validation of next-generation sequencing to support lot release for a novel type 2 oral poliovirus vaccine

Abstract: Highlights Genetic variants were evaluated to assess which were important to ensure nOPV2 quality. The cDNA preparation and NGS method was validated through evaluating mixtures of Sabin-2 and nOPV2. Pre-specified validation criteria for linearity and precision were met at all positions. The method was assessed to be fit-for-purpose for vaccine lot release. Understanding the co-location of genetic variants was important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…These are potentially relevant to neurovirulence and viral fitness, though largely anticipated from prior work studying the evolution of the Sabin-2 and nOPV2 strains. Some mutations previously identified in the nOPV2-c1 vaccine lots and characterized phenotypically 16 showed anticipated behavior upon replication in vivo. For example, VP1-E295K—which causes a temperature-sensitive defect limiting replication at 37 °C—was selected against unless compensated for by the presence of a VP1-N171D mutation.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…These are potentially relevant to neurovirulence and viral fitness, though largely anticipated from prior work studying the evolution of the Sabin-2 and nOPV2 strains. Some mutations previously identified in the nOPV2-c1 vaccine lots and characterized phenotypically 16 showed anticipated behavior upon replication in vivo. For example, VP1-E295K—which causes a temperature-sensitive defect limiting replication at 37 °C—was selected against unless compensated for by the presence of a VP1-N171D mutation.…”
Section: Discussionmentioning
confidence: 89%
“…Mutations associated with amino acid changes and meeting reporting requirements are summarized in Supplementary Table 4 . Some of these (VP3-E234K, VP1-N171D and VP1-E295K) are present at moderate levels in the vaccine lots and thus are expected to appear in shed virus 16 . For example, the level of VP3-E234K in the lot used in this study was 45%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When using attenuated strains as an alternative in IPV manufacturing, this biosafety hazard was considered significantly lower when compared with using wild-type stains. However, attenuated Sabin poliovirus strains may revert to neurovirulence before inactivation in rare cases (5′UTR nucleotide 481-G as key neurovirulence marker in Sabin PV2 [sPV2]) [15] and therefore still present a potential biosafety hazard [16] should they escape during the manufacturing process. Current manufacturing processes that use attenuated Sabin strains during vaccine production (sIPV) allow for process modernization and optimization, thereby increasing containment safety and reducing costs [17] .…”
Section: Introductionmentioning
confidence: 99%
“…It is the speed and accuracy of the NGS that allows scientists to sequence multiple genomic variants of target viruses and develop potential vaccines [ 3 ]. Additionally, NGS can ensure that genetically modified regions of the vaccine virus genome remain as designed and, in this context, a recent study confirmed NGS to be suitable for vaccine lot release [ 4 ]. NGS has proven to be indispensable during the recent COVID-19 pandemic where the progress from pathogen discovery to novel vaccine development was made in record time.…”
mentioning
confidence: 99%